The Economics of Equilibrium with Indivisible Goods - Jagadeesan, Ravi; Teytelboym, Alexander (Review of Economic Studies, 2025)
Abstract This paper develops a theory of competitive equilibrium with indivisible goods based entirely on economic conditions on demand. The key idea is to analyze complementarity and substitutability between bundles of goods, rather than merely between goods themselves. This approach allows us to formulate sufficient and essentially necessary conditions for equilibrium existence—which unify settings with complements and settings with substitutes. Our analysis has implications for auction design.